Pengaruh Promosi Terhadap Keputusan Tamu Menginap di Kyriad Hotel Bumiminang Kota Padang - Benny Fikri Yaldi; Hijriyantomi Suyuthie; Nidia Wulansari (Departemen Pariwisata Universitas Negeri Padang, 2022)
This research is a follow-up of the importance of recent promotional efforts on guests' decisions to choose to stay at hotels, this research is causal associative research. The sample in this study was 100 guests using a non-probability sampling technique. Data collection techniques by distributing questionnaires with as many as 30 statements. Furthermore, the data is processed using a simple linear regression analysis technique. The results of testing the hypothesis obtained the value of R Square with the number 0.092 which means that there is an influence of the promotion variable and the stay decision variable with a number of 9.2% and then 90.8% is influenced by other factors. regression coefficient 0.456 with Sig 0.002 < 0.05. This means that each increase of 1 promotion unit can increase 0.456 units of Stay Decision